2021
DOI: 10.1128/msystems.00725-21
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptome Sequencing and Proteomics Reveal Neonatal Ileum Dynamic Developmental Potentials

Abstract: We found previously unknown neonatal ileum developmental potentials: specific increases in undifferentiated cells, unique enterocyte differentiation, and time dependent reduction in secretory cells. Specific transcriptional factors (TFs), ligand-receptor pairs, G protein-coupled receptors, transforming growth factor β, bone morphogenetic protein signaling pathways, and the gut mucosal microbiota are involved in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…One possibility is the lower cell number of Paneth cells in intestinal epithelial cells from these species. Previous scRNA-seq surveys showed that the percentage of Paneth cells was dramatically decreased to 0.12% of all ileum epithelial cells in neonatal piglets (21 days) (Meng et al, 2021 ). In another study comprising the ileum single-cell data from Rhesus monkey, Paneth cells were not detected in ileum epithelial cells (Ziegler et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is the lower cell number of Paneth cells in intestinal epithelial cells from these species. Previous scRNA-seq surveys showed that the percentage of Paneth cells was dramatically decreased to 0.12% of all ileum epithelial cells in neonatal piglets (21 days) (Meng et al, 2021 ). In another study comprising the ileum single-cell data from Rhesus monkey, Paneth cells were not detected in ileum epithelial cells (Ziegler et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Piglet plasma, cecal mucosa, and cecal content were collected from 5 piglets at each time point: d0 (at birth; n = 5), d1 (1 d post-birth; n = 5), d7 (7 d post-birth; n = 5), d14 (14 d post-birth; n = 5), and d21 (21 d post-birth; n = 5). At each collection point, 3 samples of cecal mucosal tissue were taken: 1) cecal tissue was cut and fixed in 10% formaldehyde for processing into histochemical blocks; 2) cecal mucosa was washed thrice in PBS buffer, gently scraped, and the removed tissue was used for the isolation of single cells for scRNA-seq analysis; 3) cecal mucosa was washed thrice in PBS buffer, gently scraped, and the removed tissue was quickly frozen in liquid nitrogen, and kept in −80 °C refrigerator for proteomics and Western blotting analyses (Supplementary Figure S1A; Meng et al, 2021;Zhang et al, 2020;Zhao et al, 2020).…”
Section: Pigletsmentioning
confidence: 99%
“…Single-cell libraries were constructed using the 10x Genomics Chromium Single Cell 3′ Library and Gel Bead Kit v.2 (10 × Genomics Inc.,Pleasanton,CA,United States;1,20,237) according to the manufacturer's instructions. Protocols for single-cell sample preparation, library construction, and sequencing were performed according to our previous reports (Zhao et al, 2020;Meng et al, 2021), and that of Haber et al (2017). In summary, piglet ceca sections were collected and washed with PBS (Meng et al, 2021).…”
Section: Single Cell Isolation Library Preparation and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations